Answer:
19)
Notice that in the left side, all the numbers are powers of 2.
2 = 2^1
4 = 2^2
8 = 2^3
16 = 2^4
remember that:
(a^x)*(a^y) = a^(x+y)
then the denominator in the left is:
(2*4*8*16) = 2*(2^2)*(2^3)*(2^4) = 2^(1 + 2 + 3+ 4) = 2^8
Then we have:
then 8 + n = 0
then n = -8.
18)
here we have:
x = (x/9) + (x/6) + (x/2) + 4 + (x/12) + 2
now in the left side we can use the common factor x and write it as:
x = x*( 1/12 + 1/9 + 1/6 + 1/2) + 6
x = x*(0.861) + 6
x - x*(0.861) = 6
x*(1 - 0.861) = 6
x = 6/(1 - 0.861) = 43.2